1988
DOI: 10.1007/bf00583764
|View full text |Cite
|
Sign up to set email alerts
|

Myosin composition and functional properties of smooth muscle from the uterus of pregnant and non-pregnant rats

Abstract: The myosin heavy chain stoichiometry and the force-velocity relation have been determined in the myometrium of the non-pregnant and pregnant rat. The relative proportions of the slower migrating heavy chain (MHC1) greatly exceeded that of the faster migrating heavy chain (MHC2) as shown by electrophoresis on SDS 4%-polyacrylamide gels. The ratios of MHC1/MHC2 were 2.2/1 in the non-pregnant rats, 2.6/1 in the pregnant rat, and contrasted with 0.8/1 in the rat portal vein. This stoichiometry was unchanged by ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

1991
1991
2000
2000

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 34 publications
5
29
0
Order By: Relevance
“…In fibres contracted in the presence of calcium, there was a slight increase in myosin light chain phosphorylation with oestrogen treatment; however, this difference was not statistically significant. Sparrow et al (1988) and other previously published reports (Cavaille, Janmot, Ropert & d'Albis, 1986 of Sparrow et al (1988) from non-gravid (68-6% SMI) and gravid (71-9% SMi) rat myometrium. The increase we observed in SMI content with oestrogen treatment (65-5 to 72-9 % SMI) in ovariectomized uterus is similar, though more dramatic, than the increase in percentage SMI observed in the myometrium with pregnancy.…”
Section: Myosin Light Chain Phosphorylationsupporting
confidence: 51%
See 1 more Smart Citation
“…In fibres contracted in the presence of calcium, there was a slight increase in myosin light chain phosphorylation with oestrogen treatment; however, this difference was not statistically significant. Sparrow et al (1988) and other previously published reports (Cavaille, Janmot, Ropert & d'Albis, 1986 of Sparrow et al (1988) from non-gravid (68-6% SMI) and gravid (71-9% SMi) rat myometrium. The increase we observed in SMI content with oestrogen treatment (65-5 to 72-9 % SMI) in ovariectomized uterus is similar, though more dramatic, than the increase in percentage SMI observed in the myometrium with pregnancy.…”
Section: Myosin Light Chain Phosphorylationsupporting
confidence: 51%
“…After mounting, the fibres were slightly stretched beyond their slack length to a passive force of 0 05 mN or approximately 7 mN mm-2. This length was chosen based on experience and published uterine muscle force-length curves (Sparrow et al 1988) to obtain a reference length (L.) in the region for optimal force development. The plateau region of the force-length relation for uterine muscle is broad with only minor changes in active force between 0-8 and 1 1 of the optimal length for force development.…”
Section: Smooth Muscle Myosint Isoforms and Functionmentioning
confidence: 99%
“…However, in these studies, the presence of nonmuscle MHC in rat uterus was not reported. Sparrow et al [1988] found an equivalent SM USM2 ratio (2.2-2.6) in pregnant and nonpregnant rat uterus and no modifications in mechanical muscle parameters which could be associated with changes in MHCs. In nonpregnant uterus of mouse and swine, the SMI/SM2 ratio appeared to vary with aging, from 4.8-3.4 for the former [Eddinger and Wolf, 19931 to 4.5-1.2 for the latter [Eddinger and Murphy, 19911, associated with variations in the relative content of nonmuscle MHC(s).…”
Section: Discussionmentioning
confidence: 89%
“…Mechanical studies performed using uterus smooth muscle tissues have shown a positive correlation between SM1 myosin content and maximal velocity of muscle shortening (V max ) (Hewett et al, 1993;Sparrow et al, 1988). Cai et al (1995) showed that a 13 amino acid peptide from the unique SM1 tail decreases contractile velocity in permeabilized smooth muscle tissue, suggesting that the non-helical tail of SMHC may modulate contractility.…”
Section: Role Of Different Smhc Isoforms Tomentioning
confidence: 98%